Penyelesaian Sengketa Perceraian Publik Figur - Zahra, Salma Hauratu; Lani, Muhammad Ghiza Gema; Tarina, Dwi Desi Yayi; Adelia, Fransisca Lola; Aliffia, Nayla (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
He divorce between singer Virgoun and his ex-wife Inara Rusli has attracted significant public attention, particularly regarding complex legal, social, and moral issues. This study aims to explore various legal aspects of their divorce process, including child custody, alimony, and royalty distribution. Utilizing a normative legal approach, the research examines the legal journey from the lawsuit filed at the West Jakarta Religious Court to the appeal process at the Jakarta High Religious Court. The court's ruling granted Inara custody of their children and approved her requests for alimony and royalties. The division of joint assets, including song royalties accrued during their marriage, aligns with Article 39 of Law No. 1 of 1974 on Marriage. This case highlights the necessity for careful legal considerations in public figures' divorce disputes to protect all parties' rights, emphasizing that child welfare should be a primary concern in judicial decisions. Ultimately, the case reflects not only the legal challenges faced by divorcing couples but also broader social implications for society. This research offers valuable insights into how law can facilitate family conflict resolution under public scrutiny.